(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
For a country or area to thrive sustainably, protecting and conserving biodiversity must be a top priority on both the national and international levels. As a group, butterflies are among the most significant insects because of the roles they play as both markers of biodiversity and gardeners in nature. Worldwide, over 28,000 butterfly species have been identified. The watershed of Bansagar reservoir in Shahdol, Madhya Pradesh was the subject of a comprehensive biodiversity research that included Lepidoptera (Butterflies). As a first step in documenting biodiversity in various human-impacted wetlands, this research served as a baseline. A variety of features of forest ecology in their native habitats have been studied via the use of butterfly bionomics. In this case, assemblages of butterflies were collected from the concession and classified using diversity indices and plant type.